Canadian ROS proto-oncogene 1 study (CROS) for multi-institutional implementation of ROS1 testing in non-small cell lung cancer. (October 2021) - Cheung, Carol C.; Smith, Adam C.; Albadine, Roula; Bigras, Gilbert; Bojarski, Anna; Couture, Christian; Cutz, Jean-Claude; Huang, Weei-Yuan; Ionescu, Diana; Itani, Doha; Izevbaye, Iyare; Karsan, Aly; et al.
Highlights: High quality ROS1 IHC assays have high clinical utility. Adjusting readout can increase diagnostic accuracy in ROS1 IHC. ROS1 IHC readout must be balanced with the analytical sensitivity of the assay. A multi-institutional approach abets the validation of rare disease biomarker assays. Abstract: Patients with non-small cell lung cancer (NSCLC) harboring ROS proto-oncogene 1 ( ROS1 ) gene rearrangements show dramatic response to the tyrosine kinase inhibitor (TKI) crizotinib. Current best practice guidelines recommend that all advanced stage non-squamous NSCLC patients be also tested for ROS1 gene rearrangements. Several studies have suggested that ROS1 immunohistochemistry (IHC) using the D4D6 antibody may be used to screen for ROS1 fusion positive lung cancers, with assays showing high sensitivity but moderate to high specificity. A break apart fluorescence in situ hybridization (FISH) test is then used to confirm the presence of ROS1 gene rearrangement. The goal of Canadian ROS1 (CROS) study was to harmonize ROS1 laboratory developed testing (LDT) by using IHC and FISH assays to detect ROS1 rearranged lung cancers across Canadian pathology laboratories. Cell lines expressing different levels of ROS1 (high, low, none) were used to calibrate IHC protocols after which participating laboratories ran the calibrated protocols on a reference set of 24 NSCLC cases (9 ROS1 rearranged tumors and 15 ROS1 non-rearranged tumors as determined by FISH). Results were compared using a centralized readout. The stained slides were evaluated for the cellular localization of staining, intensity of staining, the presence of staining in non-tumor cells, the presence of non-specific staining (e.g. necrosis, extracellular mater, other) and the percent positive cells. H-score was also determined for each tumor. Analytical sensitivity and specificity harmonization was achieved by using low limit of detection (LOD) as either any positivity in the U118 cell line or H-score of 200 with the HCC78 cell line. An overall diagnostic sensitivity and specificity of up to 100% and 99% respectively was achieved for ROS1 IHC testing (relative to FISH) using an adjusted H-score readout on the reference cases. This study confirms that LDT ROS1 IHC assays can be highly sensitive and specific for detection of ROS1 rearrangements in NSCLC. As NSCLC can demonstrate ROS1 IHC positivity in FISH-negative cases, the degree of the specificity of the IHC assay, especially in highly sensitive protocols, is mostly dependent on the readout cut-off threshold. As ROS1 IHC is a screening assay for a rare rearrangements in NSCLC, we recommend adjustment of the readout threshold in order to balance specificity, rather than decreasing the overall analytical and diagnostic sensitivity of the protocols.